RETRACTED: A Synthetic Peptide Designed to Neutralize Lipopolysaccharides Attenuates Metaflammation and Diet-Induced Metabolic Derangements in Mice - Mohammad, Shireen; Al Zoubi, Sura; Collotta, Debora; Krieg, Nadine; Wissuwa, Bianka; Ferreira Alves, Gustavo; Purvis, Gareth S. D.; Norata, Giuseppe Danilo; Baragetti, Andrea; Catapano, Alberico Luigi; Solito, Egle; Zechendorf, Elisabeth; et al. (Frontiers in Immunology, 2021)
Metabolic endotoxemia has been suggested to play a role in the pathophysiology of metaflammation, insulin-resistance and ultimately type-2 diabetes mellitus (T2DM). The role of endogenous antimicrobial peptides (AMPs), such as the cathelicidin LL-37, in T2DM is unknown. We report here for the first time that patients with T2DM compared to healthy volunteers have elevated plasma levels of LL-37. In a reverse-translational approach, we have investigated the effects of the AMP, peptide 19-2.5, in a murine model of high-fat diet (HFD)-induced insulin-resistance, steatohepatitis and T2DM. Feeding mice a HFD for 12 weeks caused obesity, an impairment in glycemic regulations, hypercholesterolemia, microalbuminuria and steatohepatitis, all of which were attenuated by Peptide 19-2.5. The liver steatosis caused by feeding mice a HFD resulted in the activation of nuclear factor kappa light chain enhancer of activated B cells (NF-ĸB) (phosphorylation of inhibitor of kappa beta kinase (IKK)α/β, IκBα, translocation of NF-ĸB to the nucleus), expression of NF-ĸB-dependent protein inducible nitric oxide synthase (iNOS) and activation of the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome, all of which were reduced by peptide 19-2.5. Feeding mice, a HFD also resulted in an enhanced expression of the lipid scavenger receptor cluster of differentiation 36 (CD36) secondary to activation of extracellular signal-regulated kinases (ERK)1/2, both of which were abolished by peptide 19-2.5. Taken together, these results demonstrate that the AMP, peptide 19-2.5 reduces insulin-resistance, steatohepatitis and proteinuria. These effects are, at least in part, due to prevention of the expression of CD36 and may provide further evidence for a role of metabolic endotoxemia in the pathogenesis of metaflammation and ultimately T2DM. The observed increase in the levels of the endogenous AMP LL-37 in patients with T2DM may serve to limit the severity of the disease.